The influence of payment usage and ease of use of QRIS on customer loyalty among Gen Z (case study of UIN Raden Fatah Palembang and Sriwijaya University) - Nova Fitria; Hilda; Citra Lestari (Escalate : Economics and Business Journal, 2026)
Digital payment transformation through the Quick Response Code Indonesian Standard (QRIS) is increasing among Generation Z, but the influence of usage and ease of use on customer loyalty still shows inconsistent results in previous studies. This study aims to analyze the influence of QRIS usage and ease of use on customer loyalty among students of UIN Raden Fatah Palembang and Sriwijaya University. This study uses a quantitative approach with a survey method. The study population was Generation Z students who use QRIS at both universities, with a sample of 100 respondents selected using a purposive sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using SPSS through validity tests, reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficients of determination. The results show that QRIS usage has a positive and significant effect on customer loyalty (t = 8.540; p < 0.001), as does ease of use (t = 4.677; p = 0.002). Both variables simultaneously significantly influenced customer loyalty (F = 123.396; p < 0.001), with an explanatory power of 71.8% for the dependent variable. This study concluded that increasing the intensity of QRIS use and its ease of use can strengthen customer loyalty among Generation Z.